BIM-based green building evaluation and optimization: a case study - Guo, Kai (2022)
Green building has drawn worldwide attention due to the adverse impact of construction on the environment. This research presents a Building Information Modeling (BIM) based evaluation system for the performance assessment of green buildings. Combining BIM technology with green building analysis, the proposed approach can fully utilize the advantages of the BIM model and quickly conduct green building evaluation. A green building evaluation framework is constructed, which evaluates the green building performance from five aspects, i.e., the main building, the building envelope, the heating, ventilation and air conditioning (HVAC), the lighting and equipment, and extra points. A case study is performed to test the applicability and effectiveness of the proposed approach. Important findings are: (1) The performance of the target green building is determined as 0.87 (i.e., a fairly poor level), but it could be upgraded to 1.32 (i.e., a good level) with the consideration of extra points for the green building evaluation (2) Building renovation measures (i.e., improving the building envelop, HVAC, and lighting and equipment); could improve the performance of the green building by 31.5% on average. A synergetic impact exists among these renovation measures, where the impact of renovating all three aspects is greater than simply the sum of taking three individual measures; (3) Optimization of the green building performance could not only reduce the energy consumption but also create a more comfortable environment for the occupants, where severe conditions could be greatly reduced. The novelty of this research lies in (a) presenting a BIM-based model that is able to effectively perform the green building evaluation and optimization in a wide range and also incorporate the regional features as needed; (b) proposing a novel grading rule that makes influential factors under different standards measurable in a more intuitive manner.